Methodology of neuronal pluripotent stem cell of in vitro difference process as an alternative therapy of neurodegenerative disease - Wahyuni Wulansari; Fuad Gandhi Torizal; Annisa Khumaira; Ika Afifah Nugraheni (JHeS (Journal of Health Studies), 2022)
Neurodegenerative is diseases which occur with age but no therapeutic approach is efficient enough to inhibit neurodegenerative progression which results from aging of the cells themselves. PSC is a stem cell which has the potential to differentiate into various types of cells in the body. In the expansion process, PSC encountered problems, one of the common obstacles. This research was conducted using a literature study method that aims to obtain information about the appropriate differentiation method so that it can be used as an alternative treatment for neurodegenerative disease in the future. The result showed that 3D technique is neuronal differentiation technique that has a good output and can resemble the conditions of its development in vivo. The use of growth factors such as FGF2, PDGF, IGF1, T3, FGF, EGF, and CNTF can also overcome the problem of differentiation of several target cells in neurodegenerative therapy such as neurons, astrocytes, and oligodendrocytes.